SOSIALISASI DAN PELATIHAN APLIKASI ADMINISTRASI SEKOLAH BERBASIS WEBSITE BAGI MAHASISWA ADMINISTRASI PENDIDIKAN FKIP UNIVERSITAS PATTIMURA - Kempa, Rudolf; Rumfot, Sumarni; Sohilait, Desembra (Universitas Pattimura, 2023)
Administration is an important part of school administration. in its development, administration is carried out as effectively and efficiently as possible through various means. Technology cannot be separated in its role in developing administrative techniques and strategies in schools and others. Community service is one of the parts of the tridharma of higher education that must be carried out by lecturers as educators from higher education. Therefore, this research was developed from the results of community service by utilizing technology through websites in the administrative process. This research was carried out through a descriptive method consisting of 3 processes, namely preparation, implementation, and follow-up plans. The research, which is the result of this community service, concluded that the participants' knowledge and skills in website-based school administration governance increased. This shows the effectiveness of the training and the enthusiasm of the training participants. After the training, what was realized from this activity was (1) an increase in knowledge of the importance of web-based school administration governance, and (2) an increase in students' skills and abilities in using administrative applications (filing correspondence & infrastructure facilities).